Focal segmental glomerulosclerosis: challenges in definitions, pathogenesis and management - Feehally, John (African Journal of Nephrology, 2017)
Focal segmental glomerulosclerosis (FSGS) is a well-defined pattern of glomerular injury identifiable on renal biopsy using light microscopy. FSGS is not a single entity and much information is needed to make a proper evaluation in each subject with the condition to identify the cause, prognosticate, and inform treatment choices. Categories of information required include: clinical presentation, responsiveness to steroids, pathological subtype, genetic background, and evidence for other adaptive, viral, and toxic causes. Primary FSGS describes a cohort of conditions identified by exclusion of known contributory causes, but does not represent a single entity. Clinical manifestations and outcomes of FSGS vary widely; they include asymptomatic proteinuria, cases of spontaneous remission, steroid-sensitive nephrotic syndrome, and nephrotic syndrome resistant to immune modulating therapy progressing to end-stage renal disease with recurrence after transplantation. Although immune modulating therapy (based notably on corticosteroids and calcineurin inhibitors) are widely used in primary FSGS, robust evidence of their efficacy remains scant.